Recycling plastic - Palmer, Joy. (New York : F. Watts, 1990)
Discusses the environmental problems caused by the manufacture and disposal of plastic products and shows how the recycling of these products can reduce these threats.
Includes bibliographical references (p. 28) and index.
Booklist.
7.9
3-6
Keywords: Plastic scrap -- Environmental aspects -- Juvenile literature; Plastic scrap -- Recycling -- Juvenile literature; Plastic scrap -- Environmental aspects; Plastic scrap -- Recycling; Recycling (Waste); Refuse and refuse disposal; Plastics -- Environmental aspects; Plastics -- Recycling; Recycling; Refuse and refuse disposal